(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The aim of the research was to determine the impact of emotional marketing as an independent variable with its dimensions on customer loyalty as a dependent variable with its dimensions in the General Company for the Manufacture of Medicines and Medical Supplies / Samarra. Based on the field survey and interviews with the individuals in the research sample, the research problem was identified through a series of questions that mainly included knowing the extent to which emotional marketing affects customer loyalty. For this purpose, several hypotheses were formulated, the most important of which was that there was a direct impact of emotional marketing on customer loyalty. The researcher adopted a descriptive-analytical approach to describe and analyze the results of the research variables. The questionnaire was used as a primary tool for collecting data, in addition to conducting a set of interviews as a supporting tool. The number of respondents reached (119), in addition to conducting four interviews. The results of the questionnaire were analyzed using a set of statistical methods, the most important of which were (arithmetic mean, standard deviation, simple and multiple regression analysis). They were extracted through a set of statistical programs, including SPSS V.24, AMOS V. 24. The research concluded with a set of results, the most important of which was that there was an impact for emotional marketing in customer loyalty, while the research recommended adopting the concept of emotional marketing more to achieve customer loyalty, and thus ensuring market share and facilitating future sales forecasting.